2021
DOI: 10.1038/s41598-021-87201-2
|View full text |Cite
|
Sign up to set email alerts
|

Ocular growth and metabolomics are dependent upon the spectral content of ambient white light

Abstract: Myopia results from an excessive axial growth of the eye, causing abnormal projection of remote images in front of the retina. Without adequate interventions, myopia is forecasted to affect 50% of the world population by 2050. Exposure to outdoor light plays a critical role in preventing myopia in children, possibly through the brightness and blue-shifted spectral composition of sunlight, which lacks in artificial indoor lighting. Here, we evaluated the impact of moderate levels of ambient standard white (SW: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…1 B), promoted a recovery from myopic refractive error to measures that were not significantly different from control eyes on D28 of the experimental protocol. Previous reports have also shown that blue-enriched white light (CCT = 9700 K) can slow axial elongation induced by FDM, and accelerate recovery from FDM in a chicken model, 26 whereas a recent study by Yoon et al 36 demonstrated that exposure to 985 lux of broad-spectrum light with a high blue content can slow axial elongation in chicks. Whether the effect of blue-enriched white light on recovery from experimental myopia is only due to LCA 46 or other additional phenomena remains unclear.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1 B), promoted a recovery from myopic refractive error to measures that were not significantly different from control eyes on D28 of the experimental protocol. Previous reports have also shown that blue-enriched white light (CCT = 9700 K) can slow axial elongation induced by FDM, and accelerate recovery from FDM in a chicken model, 26 whereas a recent study by Yoon et al 36 demonstrated that exposure to 985 lux of broad-spectrum light with a high blue content can slow axial elongation in chicks. Whether the effect of blue-enriched white light on recovery from experimental myopia is only due to LCA 46 or other additional phenomena remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“… 30 Although many investigations have focused on the impact of intense light on experimental myopia development, 31 35 only a few have investigated the impact of the spectral characteristics of ambient, moderate intensity, visible white light on refractive error development. 15 , 26 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…130132 Furthermore, ocular DA release and metabolism, as well as vitreal and retinal metabolomic profiles, were highly dependent upon the spectral composition of light. 132,133 Among plausible explanations to this wavelength-dependent refractive error regulation, ocular longitudinal chromatic aberration (LCA), which leads to wavelength defocus and higher refraction of short-wavelength light compared with long-wavelength light by ocular optics, was supported by many authors. 131,134,135 The hyperopic shift in response to short-wavelength blue light has also been reported in other, but not all, animal species such as Cichlid fish, 136 guinea pigs 137141 and some rhesus monkeys.…”
Section: Experimental Research On Light and Myopiamentioning
confidence: 99%
“…sleep, alertness, melatonin secretion at night) (for review, see Najjar and Zeitzer 231 ). Melanopsin is predominantly sensitive to bright blue light (~480nm), a wavelength reported to induce hyperopia and reverse experimental myopia in some animal models 130133 and the increase in ocular DA levels upon bright light exposure could potentially be due to the stimulation of melanopsin and the synaptic and functional connection between the ipRGCs and dopaminergic amacrine cells. 232,233 In addition, melanopsin knockout mice display a decline in ocular DA levels, 234 and preliminary findings highlight a direct, yet unclear, role of melanopsin in refractive error development.…”
Section: Physiological Mechanisms Mediating Light-induced Myopia Preventionmentioning
confidence: 99%